Uma investigação sobre a inserção da Educação Financeira em um Curso de Serviço de Matemática Financeira para graduandos de um curso de Administração A research about the insertion of Financial Education in a Course of Service of Financial Mathematics for undergraduate students of an Administration course - Kistemann, Marco Aurélio; Teixeira, Wesley Carminati (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2017)
A pesquisa descrita neste artigo, de caráter qualitativo, tem como temática central a Educação Financeira. O objetivo nele proposto é o de investigar se a aplicação de um Curso de Serviço de Matemática Financeira, para estudantes do Ensino Superior, de um curso de Administração, que inclua em seu bojo temas da Educação Financeira, pode despertar um espírito crítico, nas tomadas de decisões e posturas, destes futuros administradores inseridos numa sociedade de consumo. Nos inspiramos teoricamente nas ideias da Educação Matemática Crítica, nas pesquisas em Educação Financeira de Kistemann Jr. (2011), sobre a produção de significados e as tomada de decisão de indivíduos-consumidores. Foi utilizado o Estudo de Caso como metodologia de pesquisa qualitativa, embasado nos trabalhos de Ponte e de Yin, que validaram as análises dos perfis dos sujeitos de pesquisa e das respostas encontradas nas atividades desenvolvidas. The research described in this article, of a qualitative nature, has as its central theme the Financial Education. The goal of this study was to investigate whether the application for a course of service of Financial Mathematics, with themes of financial education for students in higher education from a course of the Administration, could awaken a critical spirit, in decision making, these future administrators. Our theoretical inspirations are the ideas of Mathematics Education criticism, in research on Financial Education of Kistemann Jr. (2011), Costa (2012), Hermínio (2008), Campos (2013), Barroso (2013), Resende (2013) and Teixeira (2015). We used the Case Study as a qualitative research methodology, based on the work of Ponte and Yin, which validated the analyses of the profiles of the study subjects and the responses found in the activities undertaken. As the main result of this research highlights the educational product "the insertion of financial education in a course of service of Financial Mathematics, for students of a course in Administration" which had as main objective to propose an alternative to the teaching and learning of mathematical finance in higher education, with the presentation of scenarios for research, with themes concerning the consumption and use of financial instruments